Prevalence, clinical and prognostic value of polymorphism of genes II, V factors of blood coagulation and methylenetetrahydrofolate reductase in patients with chronic kidney disease - O. A. Pavlenko; T. A. Kolosovskaya; O. F. Sibireva; Ye. Yu. Khitrinskaya; V. Yu. Grankina; V. V. Kalyuzhin (Бюллетень сибирской медицины)
The aim of the investigation was to study the prevalence, clinical and prognostic values of polymorphism of genes II, V factors of blood coagulation and methylenetetrahydrofolate reductase in patients with chronic kidney disease. Examination was performed on 90 patients with diabetic nephropathy (DN) and 180 patients with chronic glomerulonephritis (CG). In addition to complete clinical and instrumental examination accepted in specialised clinic, with the help of polymerase chain reaction diagnostics of polymorphism of the referred above genes (samples of genomic DNA were obtained from peripheral blood leukocytes) was conducted. It was found that the protrombogenic mutations under investigation which are detected in patients with DN and CG more often than in healthy subjects are associated with development of hypercoagulation syndrome and higher risk of renal failure.